(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Traditional Ecological Knowledge (TEK) represents a cumulative body of wisdom developed by indigenous communities through generations of interaction with their environment. This study explores how TEK can be leveraged for sustainable environmental practices in Cross River State, Nigeria, a region rich in biodiversity yet facing ecological degradation due to deforestation, climate change, and unsustainable land use. Using primary data collected through semi-structured interviews, focus group discussions, and participant observation with 150 participants from three communities (Obanliku, Akamkpa, and Calabar South), the research identifies TEK practices such as sacred grove conservation, rotational farming, and taboo-based resource management. Findings reveal that these practices enhance biodiversity conservation, soil fertility, and community resilience. However, challenges including modernization, land tenure conflicts, and erosion of cultural knowledge threaten TEK’s efficacy. The study employs a cultural ecology theoretical framework to analyze the interplay between human practices and environmental sustainability. A comprehensive literature review situates the research within global and regional TEK scholarship, highlighting its relevance to sustainable development goals (SDGs). Recommendations include integrating TEK into state environmental policies, documenting indigenous knowledge, and fostering community-led conservation initiatives. This study underscores TEK’s potential as a cost-effective, culturally resonant tool for sustainable environmental management in Cross River State.